Effectiveness of sacubitril–valsartan in cancer patients with heart failure. (5th February 2020) - Martín‐Garcia, Ana; López‐Fernández, Teresa; Mitroi, Cristina; Chaparro‐Muñoz, Marinela; Moliner, Pedro; Martin‐Garcia, Agustin C.; Martinez‐Monzonis, Amparo; Castro, Antonio; Lopez‐Sendon, Jose L.; Sanchez, Pedro L.
Abstract: Aims: Current guidelines recommend sacubitril/valsartan for patients with heart failure and reduced left ventricular ejection fraction (LVEF), but there is lack of evidence of its efficacy and safety in cancer therapy‐related cardiac dysfunction (CTRCD). Our aim was to analyse the potential benefit of sacubitril/valsartan in patients with CTRCD. Methods and results: We performed a retrospective multicentre registry (HF‐COH) in six Spanish hospitals with cardio‐oncology clinics including all patients treated with sacubitril/valsartan. Demographic and clinical characteristics and laboratory and echocardiographic data were collected. Median follow‐up was 4.6 [1; 11] months. Sixty‐seven patients were included (median age was 63 ± 14 years; 64% were female, 87% had at least one cardiovascular risk factor). Median time from anti‐cancer therapy to CTRD was 41 [10; 141] months. Breast cancer (45%) and lymphoma (39%) were the most frequent neoplasm, 31% had metastatic disease, and all patients were treated with combination antitumor therapy (70% with anthracyclines). Thirty‐nine per cent of patients had received thoracic radiotherapy. Baseline median LVEF was 33 [27; 37], and 21% had atrial fibrillation. Eighty‐five per cent were on beta‐blocker therapy and 76% on mineralocorticoid receptor antagonists; 90% of the patients were symptomatic NYHA functional class ≥II. Maximal sacubitril/valsartan titration dose was achieved in 8% of patients (50 mg b.i.d.: 60%; 100 mg b.i.d.: 32%). Sacubitril/valsartan was discontinued in four patients (6%). Baseline N‐terminal pro‐B‐type natriuretic peptide levels (1552 pg/mL [692; 3624] vs. 776 [339; 1458]), functional class (2.2 ± 0.6 vs. 1.6 ± 0.6), and LVEF (33% [27; 37] vs. 42 [35; 50]) improved at the end of follow‐up (all P values ≤0.01). No significant statistical differences were found in creatinine (0.9 mg/dL [0.7; 1.1] vs. 0.9 [0.7; 1.1]; P = 0.055) or potassium serum levels (4.5 mg/dL [4.1; 4.8] vs. 4.5 [4.2; 4.8]; P = 0.5). Clinical, echocardiographic, and biochemical improvements were found regardless of the achieved sacubitril–valsartan dose (low or medium/high doses). Conclusions: Our experience suggests that sacubitril/valsartan is well tolerated and improves echocardiographic functional and structural parameters, N‐terminal pro‐B‐type natriuretic peptide levels, and symptomatic status in patients with CTRCD.